Pleasure and pedagogic discourse in school mathematics : a case study of a problem-centred pedagogic modality - Davis, Zain (School of Education, 2017)
thesis is concerned with the production of an account of the relation between the reproduction of specialised knowledge and the moral discourse within pedagogic practice. The internal mechanism that knots together knowledge and moral discourse is elaborated by way of an analysis of texts produced by the originators of a pedagogic modality they refer to as the "problem-centred approach." The particular texts analysed are: (1) the Grade 1 to 4 textbooks and the corresponding teacher's guides, and (2) video records, supplied by the originators, of what they consider to be exemplary realisations of the pedagogy in practice of the "approach." The thesis opens with a discussion of a proposition, derived from Bernsteinian studies of curriculum and pedagogy, stating that everyday and academic know ledges are incommensurable, and from which it is claimed that the insistent contemporary attempts at incorporating the everyday into the academic in curricula and pedagogy, under the banner of "relevance," are educationally problematic. Against the Bernsteinian position, a central feature of the "problem-centred approach" is the extensive recruitment of extra-mathematical referents for the purposes of the reproduction of school mathematics. A more general examination of school mathematics texts that recruit the everyday reveal that such texts also associate the everyday with the pleasure of the student, so rendering "relevance," and hence moral discourse, as utilitarian. The manner in which the moral discourse operates within pedagogy was described in terms of Hegel's theory of judgement and Freudian-Lacanian accounts of imaginary and symbolic identification. Hegel enabled a description of pedagogic discourse at the level of the instructional content, and Freud-Lacan at the level of moral discourse. Hegel also enabled the location of the point at which the moral attaches to the instructional. What our analysis revealed is as follows: (1) the "problem-centred approach" is a competence-type pedagogy that employs strategies encouraging an initial imaginary identification with the everyday and pleasure, which is used to effect symbolic identification with school mathematics; (2) moral discourse drives pedagogic judgement by means of the imaginary-symbolic dialectic pertaining to identification; (3) evaluation drives pedagogic judgement aimed at the knowledge statements produced by students; and that (4) while the moral discourse is a pervasive and formally necessary component of pedagogy, it is ultimately embedded in the organisation and elaboration of the instructional contents, working in the service of the reproduction of instructional contents, but in accord with dominant ideological imperatives.